Remote sensing with GIS techniques in monitoring wheat grain beetle, Anisoplia sp. to evaluate the severity of wheat infestation in Erbil Province - Sahand K. Khidr; Srwa M. Khalil (Zanco Journal of Pure and Applied Sciences)
This study was undertaken to monitor and assess the distribution of the wheat chafer, Anisoplia sp. and to determine how severe wheat crop could be infested by the beetle, utilizing both traditional field surveys and Geographic Information Systems (GIS) technology. The beetle is a destructive soil pest that causes severe damage to various cereal crops. Thus, the study analyzed key soil parameters including (soil texture, EC, pH, organic matter) and crop biological parameters including (chlorophyll content, water content, and Leaf Area Index) to assess the health of wheat crops and the impact of beetle infestation. The larval stage was collected from wheat fields across twelve villages located in the four directions of Erbil (North, East, West and South) in various period of time (November, January, and March), and GIS data was used to map the spatial distribution of infestations. Results indicated significant variation in the beetle population density and severity of wheat infestation across different geographic locations, with the highest levels of 7.51 larvae /M2 and 54.39% wheat infestation observed in villages located in the West direction of Erbil. Further, January 2023 attained the highest larvae population, 7.32 larvae /M2. The population density of the larvae correlated with both the texture and organic matter of the soil. GIS-based mapping revealed correlations between field-collected data and remote sensing parameters, enabling accurate prediction of infestation severity. The study demonstrates the potential of integrating traditional and modern techniques to monitor pest populations and improve pest management strategies in wheat production.